Assessment of pre-service teachers’ satisfaction on the frequency and mode of ICT use in teacher training programmes in Nigerian universities (2021)
In compliance with the realities of an Information and Communication Technology (ICT)-driven society and global indexes in terms of quality assurance in university education, the use of ICT has been integrated into the Nigerian university system. In Nigeria, university education has received the most attention in terms of funding, technical support and policy reengineering. With the inevitable rise in ICT-based instruction globally, National Universities Commission (NUC) emphasized the use of ICT in Nigerian universities. Thus, ICT was integrated into teacher-training programmes in most Nigerian universities with huge investments made in staff training, internet connectivity, interactive smart boards, multimedia projectors and other e-learning channels. In spite of these, the use of ICT resources by university lecturers has been inconsistent or nonexistent largely due to lecturer-related variables such as age, gender and exposure. This has dire implications for pre-service teachers' satisfaction on the use of ICT in teacher-training. Therefore, this study examines pre-service teachers' satisfaction on the frequency and mode of ICT use in teacher-training in University of Ibadan. Seven research questions are raised and data were collected with ICT using online survey comprisingl40 participants. The results shows that pre-service teachers are not satisfied with frequency and mode of ICT use in teacher education. The study also found that younger lecturers make use of ICT-resources more than the older colleagues in Nigerian Universities. Regular training of lecturers on the use of ICT and improved power supply are recommended for optimal gains in the integration of ICT in teacher education.